2020
DOI: 10.1021/acsami.0c17811
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Photoelectrochemical Water Splitting Using GaN-Nanowire Photoanode with Tungsten Sulfides

Abstract: In the present study, we have achieved high-performance photoelectrochemical water splitting (PEC-WS) using GaN nanowires (NWs) coated with tungsten sulfide (W x S 1−x ) (GaN-NW-W x S 1−x ) as a photoanode. The measured current density and applied-bias photon-to-current efficiency were 20.38 mA/cm 2 and 13.76%, respectively. These values were much higher than those reported previously for photoanodes with any kind of III-nitride nanostructure. The amount of hydrogen gas formed was 1.01 mmol/cm 2 from 7 h PEC-W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 74 publications
0
25
0
Order By: Relevance
“…This result is consistent with the peak wavelength measured at the PL spectrum of GaN NWs. Considering these results, the carriers were effectively generated by illuminating light to the stretchable GaN-NW photosensors . The EQE exceeding 100% can be explained by the high carrier mobility afforded by the graphene channel .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This result is consistent with the peak wavelength measured at the PL spectrum of GaN NWs. Considering these results, the carriers were effectively generated by illuminating light to the stretchable GaN-NW photosensors . The EQE exceeding 100% can be explained by the high carrier mobility afforded by the graphene channel .…”
Section: Resultsmentioning
confidence: 93%
“…Considering these results, the carriers were effectively generated by illuminating light to the stretchable GaN-NW photosensors. 43 The EQE exceeding 100% can be explained by the high carrier mobility afforded by the graphene channel. 44 Yao et al reported that the photogenerated carriers can cycle through the graphene channel several times with the help of an external voltage.…”
Section: Resultsmentioning
confidence: 99%
“…As an ideal secondary energy source, hydrogen energy ( i.e ., the chemical energy stored in hydrogen gas) has attracted worldwide attention due to its unique advantages, including high gravimetric energy density (∼140 MJ kg –1 ), zero-emission feature, and so on. Over 90% of the global hydrogen production, nevertheless, is still dependent on fossil fuel-related routes, such as steam reforming of natural gas, which is associated with high pollution and intensive energy consumption. Obviously, this has become the major bottleneck for the utilization of hydrogen energy. , Consequently, developing an eco-friendly and energy-efficient route to produce hydrogen gas is essential for the long-term and sustainable utilization of hydrogen energy.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Most importantly, the conduction-band minimum and valance-band maximum of GaN can straddle the water redox potentials, facilitating a negative onset potential. [25][26][27][28] Among these materials, GaN nanowires (NWs) have been considered as an effective photoanode material to improve the PEC-WS performance because of their large surface-to-volume ratio and strong charge separation characteristics. 26 However, GaO x , which forms on the GaN surface by native oxidation, acts as carrier trap sites, which introduce upward surface energy-band bending.…”
mentioning
confidence: 99%
“…[25][26][27][28] Among these materials, GaN nanowires (NWs) have been considered as an effective photoanode material to improve the PEC-WS performance because of their large surface-to-volume ratio and strong charge separation characteristics. 26 However, GaO x , which forms on the GaN surface by native oxidation, acts as carrier trap sites, which introduce upward surface energy-band bending. This lowers the probability of extracting photogenerated carriers to the electrolyte, resulting in the degradation of the PEC-WS performance, including the STH.…”
mentioning
confidence: 99%